Effectiveness and maintenance of behavior change and exercise programs on depressive symptoms in older adults - Lucelia Borges; Simone Meurer; Tânia Benedetti (Revista Brasileira de Atividade Física e Saúde)
The aim of the study was to compare the effectiveness and maintenance of two health promotion programs on depressive symptoms (DS) of older adults. The research was conducted with the network of primary health care in a southern capital of Brazil. In total, 119 older adult participants were allocated into different groups: behavior change (BCG; n=40), exercise (EG; n=51) and control (CG; n=28), assessed at baseline (A1) and followed-up at three (A2), six (A3) and twelve months (A4). BCG attended "VAMOS – Vida Ativa Melhorando a Saúde” (in English, Active Living Improving Health) program while EG attended aerobic gymnastic sessions. The DS were measured by the Geriatric Depression Scale (GDS-15) and level of physical activity (LPA) through accelerometers. Results show that only BCG reduced the number of older adults with high DS (A1=9; A2=4) and this reduction was maintained after six (A3=3) and twelve months (A4=4). Six older adults became physically active (BCG=3; EG=2; CG=1) after the intervention. However, there was no LPA maintenance after six and twelve months, once the frequency of insufficiently active older adults increased or was similar to baseline. When comparing DS, an interaction was found between group and assessment (F=2.94, p=0.01) for BCG, highlighting the reduction (A1=4.0; A2=2.5) and maintenance (A3=2.6; A4=2.8) of mean DS in this group. The results indicate that behavior change programs may bring benefits to the mental health of older adults and the VAMOS program seems to be a viable option for older adults in the community.